The intracranial-B2LEED3S Score and the Risk of Intracranial Hemorrhage in Ischemic Stroke Patients Under Antiplatelet Treatment - Amarenco, Pierre; Hennerici, Michael G. (Cerebrovascular diseases, 2017)
Background: Chronic antiplatelet therapy in the post-acute phase of non-cardioembolic ischemic stroke is limited by the risk of intracranial hemorrhage (ICH) complications. Methods: We developed an ICH risk score based on the PERFORM trial cohort (n = 19,100), which included patients with a non-cardioembolic ischemic stroke or transient ischemic attack, and externally validated this score in one contemporary trial of very similar size and inclusion criteria, the PRoFESS trial (n = 20,332 patients). Outcome was ICH over 2 years. A Cox proportional-hazard regression analysis identified risk factors. Discrimination was quantified with c-statistics and calibration was assessed by comparing predicted and observed ICH risk in PERFORM and PRoFESS. Results: ICH occurred within 2 years in 263 (1.4%) patients in PERFORM trial and in 246 (1.2%) patients in PRoFESS trial. A 13-point score based on 9 items (Intracranial-B2LEED3S score - low body mass index, blood pressure, lacune, elderly, Asian ethnicity, coronary artery or cerebrovascular disease history, dual antithrombotic agent or oral anticoagulant, gender) was derived from the PERFORM trial. In PERFORM, the observed 2-year ICH risk varied from 0.75% in low-risk (score ≤2) to 2.44% in high-risk patients (score ≥5) with an acceptable calibration but a low discrimination both in PERFORM (c-statistic 0.64, 95% CI 0.61-0.68) and on external validation in PRoFESS (0.58, 95% CI 0.55-0.62). Conclusion: The Intracranial-B2LEED3S score helps identify patients who are at a high risk of bleeding. However, other variables need to be identified to improve the score (e.g., microbleeds) (Clinical Trial Registration Information ISRCTN66157730). URL: http://www.isrctn.com/ISRCTN66157730?totalResults=5&pageSize=10&page=1&searchType=basic-search&offset=3&q=&filters=conditionCategory%3ACirculatory+System%2CrecruitmentCountry%3ATaiwan%2CrecruitmentCountry%3AAustria&sort=.
Gesehen am 29.03.2018